WAIS Divide Core 10Be data, 2850-3240 m - Caffee, Marc; Welten, Kees; Woodruff, Thomas (IEDA: US Antarctic Program Data Center, 2023)
This dataset contains a continuous depth profile of 10Be measured in ice core samples from the WAIS Divide Core between 2850 and 3240 m depth.